Almadrava: a proposal for a touristic revival - Batista, Nuno (2022)
It was very common to see the establishment of the tuna’s fishermen in the Algarvian beaches, from April to June or August. The Arraiais (fishing yards) in the sand, strategically placed near the Almadravas (tuna nets) placed in the sea, had their own socioeconomic relations and their own temporary urban landscape. In this paper, it is elaborated a touristic proposal, based in the tuna fishing theme. There are almost no offers for touristic proposals, based in tuna fishing heritage, in Algarve. We believe that this may be an alternative to the high season, because of its meaning during the tuna fishing season and, due to Algarve geographical location, it is also related to the Mediterranean Diet. This proposal can enhance the awareness of the loss of this heritage, being a way of spreading and reviving something that has been lost and forgotten.